Is the Public Private Partnership Model the Right Vehicle for Public Infrastructure Delivery in Developing Countries? - Patrick Mabuza (Journal of Economics and Behavioral Studies, 2019)
There has been an increase in the number of governments that adopted public-private partnership (PPP) as an infrastructure delivery model. However, there are still misgivings about the role PPPs play in developing countries’ economies. The objective of this study is to address the question of whether the PPP model really benefits the public. This study follows a qualitative approach based on international review of literature on PPP experiences around the world. The results of the study indicate that, the PPP model can be a good vehicle for delivering public infrastructure projects in developing countries. However, for PPPs to meet the expectations of the public sector and the citizens there are certain aspects that need to be in place i.e. transparency, accountability, optimum risk allocation/sharing, and increased competition to name just a few. If a country implements its PPP programme properly, there are massive benefits compared to the public procurement approach that may accrue to consumers and the economy as a whole. Such benefits include reduced prices, which may also increase access to services. The study has elucidated valid from invalid arguments about PPPs and has established whether the PPP model is indeed the right vehicle for delivering infrastructure projects.